2013
DOI: 10.1068/i0565
|View full text |Cite
|
Sign up to set email alerts
|

The Binocular Advantage in Visuomotor Tasks Involving Tools

Abstract: We compared performance on three manual-dexterity tasks under monocular and binocular viewing. The tasks were the standard Morrisby Fine Dexterity Test, using forceps to manipulate the items, a modified version of the Morrisby test using fingers, and a “buzz-wire” task in which subjects had to guide a wire hoop around a 3D track without bringing the hoop into contact with the track. In all three tasks, performance was better for binocular viewing. The extent of the binocular advantage in individuals did not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…With this in mind, the present study constitutes an important first step toward the development of a clinically useful test of dynamic stereoacuity to reflect realworld interactions with depth. [42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, the present study constitutes an important first step toward the development of a clinically useful test of dynamic stereoacuity to reflect realworld interactions with depth. [42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving simple prehensile and buzz-wire tasks have shown a binocular advantage in almost every indicator of performance for stereo-normal participants, concluding that there is a significant loss of visual information associated with monocular viewing. 9 10 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Read et al (2013) report that subjects (aged 7–82) performed manual dexterity tasks faster and more accurately with both eyes open than with one eye occluded, but the binocular advantage was not significantly correlated with their stereoacuity. Similarly, Murdoch, McGhee, and Glover (1991) reported that while individuals with no stereopsis have difficulty in performing a task with 3D clues, there are some individuals (post-fellowship ophthalmologists) who “have better manual dexterity than one might anticipate on the basis of stereoacuity testing alone”.…”
Section: Why Does Stereopsis Matter?mentioning
confidence: 99%